Pondering on Problems of Argumentation
XXII, 306 p.
Keywords: Pondering on Problems of Argumentation is a collection of twenty essays brought together for anyone who is interested in theoretical issues in the study of argumentation. This collection of papers gives the reader an insightful and balanced view of the kind of theoretical issues argumentation theorists are currently concerned with. Because most of the perspectives on argumentation that are en vogue are represented, this volume provides a multidisciplinary and even interdisciplinary outlook on the current state of affairs in argumentation theory. Some of the contributions in Pondering on Problems of Argumentation deal with problems of argumentation that have been recognized as theoretical issues for a considerable time, like the problems of fallaciousness and identifying argumentation structures. Other contributions discuss issues that have become a focus of attention only recently or regained their prominence, such as the relationship between dialectic and rhetoric, and the strategic use of the argumentative technique of dissociation. In five separate sections papers are included dealing with argumentative strategies, problems of norms of reasonableness and fallaciousness, types of argument and argument schemes the structure of argumentation and rules for advocacy and discussion. .